2001
DOI: 10.1080/obs.80.11.1051.1055
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and seeking help in women with urinary incontinence: A population-based study

Abstract: The QoL, in this female general population, is more affected by women with urge incontinence than women with stress incontinence. Help seeking is associated with substantially lower QoL scores and with urge incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 15 publications
5
83
3
3
Order By: Relevance
“…This small difference could be explained by the group of women with persistent incontinence being made up of a large proportion of women with stress incontinence (77%) still after 4 years, a symptom that to some extent is avoidable. In our previous study, using consultation as an indicator of bothersomeness of the UI a change greater than 13 Á/22 points in any SF-36 dimension was interpreted as clinically meaningful (11). Other investigators have suggested a change of around 20 QoL points for any of the 8 dimensions as being clinically important with this instrument (12,14).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This small difference could be explained by the group of women with persistent incontinence being made up of a large proportion of women with stress incontinence (77%) still after 4 years, a symptom that to some extent is avoidable. In our previous study, using consultation as an indicator of bothersomeness of the UI a change greater than 13 Á/22 points in any SF-36 dimension was interpreted as clinically meaningful (11). Other investigators have suggested a change of around 20 QoL points for any of the 8 dimensions as being clinically important with this instrument (12,14).…”
Section: Discussionmentioning
confidence: 98%
“…These women had participated earlier in a prevalence study performed in 1995 (3), and in a QoL study performed in 1996 (11). To enhance the response rate, two postal reminders were sent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress urinary incontinence affects up to 30% of women after their first vaginal childbirth [3] and up to 50-65% after menopause [4]. Validated questionnaires have demonstrated that both major incontinence types within the female population-''stress urinary incontinence'' and ''urge urinary incontinence''-confer strongly negative effects on quality of life [5,6,7,8,9]. As our understanding of incontinence continues to evolve, and to most effectively focus efforts at primary prevention, there is an ongoing need to identify women who are significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 This, in turn, may compound other reasons why women are reluctant to discuss UI with others, such as embarrassment, the idea that UI is normal, or a perceived lack of providers' priority for evaluating or treating UI. 9,50,51 Freelists have been used to examine these types of cultural differences among patients, faculty, and medical residents 48 ; we believe this is a promising area for future research focused on women with long-term UI and the healthcare providers they are most likely to encounter, including primary and specialty care clinicians.…”
Section: Figmentioning
confidence: 99%